Students’ Knowledge Regarding Antibiotic Usage for Children Upper Respiratory Tract Infections (Unnes Journal of Public Health, 2022)
Upper respiratory tract infections are the most common illness among children under 5 years old. Knowledge regarding antibiotics usage is essential especially among pharmacy and nursing students. To assess students' knowledge regarding the use of antibiotics to treat children upper respiratory tract infection (URTIs). A cross-sectional study was conducted on 300 students collected from the College of Nursing and Pharmacy in a private university in Baghdad using convenience sampling. Data collection was done using an electronic platform. Around two-thirds (58.7%) of the students have a good level of knowledge. Only (41.3%) of students had poor knowledge about the use of antibiotics in children's upper respiratory tract infections. More than half (60.33%) of the students were aware of antibiotic resistance resulting from the overuse of antibiotics. There was a significant association between gender and Knowledge on antibiotics usage (P value=0.022). The students' knowledge regarding the use of antibiotics to treat children upper respiratory tract infection was good. More health promotions and educational campaigns are required to help students understand the correct use of antibiotics.